2007
DOI: 10.1590/s1980-57642008dn10300007
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity and applicability of the Brazilian version of the Brief Assessment of Cognition in Schizophrenia (BACS)

Abstract: Cognitive assessment in schizophrenia has traditionally used batteries that are long and complex or differ widely in their content. The Brief Assessment of Cognition in Schizophrenia (BACS) has been developed to cover the main cognitive deficits of schizophrenia as well as to be easily and briefly administered, portable, sensitive and reliable.ObjectivesTo investigate the applicability and sensitivity of the Brazilian Version of the BACS (Brazilian-BACS).MethodsPerformance of 20 stable patients with schizophre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 15 publications
2
15
0
2
Order By: Relevance
“…The first component also correlated significantly with each of the test constructs, suggesting that a one-factor solution best fits our data. The same solution was obtained in our pilot study of the BACS ( 12 ) and in studies of the Spanish and Persian versions ( 9 , 11 ), while the French version found a two-factor solution ( 6 ), and the original test in English and the Japanese version found a three-factor solution ( 3 , 7 ). This variance in the component analysis among these studies may be related to the differences in their samples ( 9 ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…The first component also correlated significantly with each of the test constructs, suggesting that a one-factor solution best fits our data. The same solution was obtained in our pilot study of the BACS ( 12 ) and in studies of the Spanish and Persian versions ( 9 , 11 ), while the French version found a two-factor solution ( 6 ), and the original test in English and the Japanese version found a three-factor solution ( 3 , 7 ). This variance in the component analysis among these studies may be related to the differences in their samples ( 9 ).…”
Section: Discussionsupporting
confidence: 72%
“…The adaptation of the BACS to Brazilian Portuguese is described elsewhere ( 12 ). The constructs measured with the Brazilian version of the BACS, including the tests, procedures, and measures, are listed below in the order of administration.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Outras baterias foram desenvolvidas com o objetivo de ser breves e de fácil administração. Uma dessas baterias encontra-se validada no Brasil: a Brief Assessment of Cognition in Schizophrenia (BACS) 14 , que cobre a maioria dos défi cits cognitivos da esquizofrenia. Os domínios cognitivos avaliados são memória verbal, memória de trabalho, velocidade motora, atenção, solução de problemas e fl uência verbal.…”
Section: Avaliação Das Alterações Cognitivasunclassified
“…Em geral, são avaliações objetivas, extensas, destinadas ao emprego em situações de pesquisa. Mais recentemente, têm sido desenvolvidos testes específicos para a avaliação cognitiva de pacientes com esquizofrenia de aplicação mais simples e duração mais curta, por exemplo, a Brief Assessment of Cognition in Schizophrenia (BACS), já traduzida para o português e avaliada em nosso meio 10 . Entretanto, alguns autores questionam se os resultados desses testes objetivos seriam evidência suficiente para avaliação de melhora cognitiva em estudos clínicos 11 .…”
Section: Introductionunclassified